Determinasi Effective Tax Rate pada Perusahaan Subsektor Kimia di Bursa Efek Indonesia - Wulan Nadirawati; Reika Happy Sugiastuti (Universitas Muhammadiyah Jakarta, 2026)
Objectives: This study aims to analyze the determinants of the Effective Tax Rate through leverage, liquidity, and profitability in chemical subsector companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Design/method/approach: This study employs a quantitative method using secondary data and a purposive sampling technique, resulting in a sample of eight companies. Data were analyzed using multiple linear regression with SPSS 25. Results/findings: The results indicate that leverage and profitability have a significant effect on the Effective Tax Rate, while liquidity does not have a significant effect on the Effective Tax Rate. Theoretical contribution: This study enriches the literature on the application of agency theory by explaining the influence of leverage, liquidity, and profitability on the Effective Tax Rate in chemical subsector companies Practical contribution: The findings provide insights for company management in evaluating capital structure, liquidity, and profitability to optimize tax management. They are also useful for investor, financial analysts, and the Directorate General of Taxes in assessing corporate tax risk and supporting tax compliance monitoring. Limitations: This study is limited to chemical subsector companies listed on the Indonesia Stock Exchange during the 2021-2025 period.